An Analysis Of Sense Based Sentences In Lenka Album - JANNAH., MIFTAHUL (2012)
This research aims to describe the kinds of sense based sentences and describe the meaning of sense based sentence found in Lenka Album. The research type conducted by the writer is descriptive qualitative research. The data of this research are simple declarative sentences found in Lenka Album, while the data source of this research is taken from the manuscript of song lyrics of Lenka Album. The writer employs documentation as the method of collecting data with the steps: reading, underlying, rewriting, and coding the data. In analyzing the data, the writer describes the kinds of sense based sentences found in Lenka Album by referring to the theory of sense properties of sentences by Hurford and Heasley (1983) and describes the meaning of sense based sentence found in Lenka Album by referring to contextual meaning. The result of this research shows that there are three kinds of sense based sentences from thirty nine data found in Lenka Album. They are analytic sentence (7 data/ 17, 95 % ), synthetic sentence (31 data/ 79, 49 %), and contradiction sentence (1 datum/ 2, 56 %). The meaning of sense based sentence is described by referring to contextual meaning which can be either directly or indirectly inferred from the sentence analyzed.